Urban Upgrading in Latin America and the Caribbean - Cira, Dean A. (World Bank, Washington, DC, 2012)
The proliferation of urban slums is due in large part to obsolete regulatory, legal and institutional frameworks at the local level governing land use, development standards, land registration and titling. These regulations are often exclusionary, insisting on development norms and standards that are outside the realm of the poor to pay and subdivision procedures are often over burdensome, leading to informal land subdivision, thus excluding the possibility to register titles under such "illegal" conditions. Likewise, well intentioned federal or national housing policies that focus on the provision of complete housing packages (as opposed to products like sites and services, progressive housing or demand, rather than supply-side subsidies) often have the unintended effect of filtering-up to higher income groups, especially when private mortgage market alternatives are not available to middle and lower-middle class households. Reforming these structural problems remains one of the greatest challenges, but progress is being made in countries like Brazil, Mexico on both the land and housing sides, and in Venezuela with regard to land and development standards.